กระบวนการทางเอนไซม์สำหรับแปรรูปไซรัปกล้วยหอม Musa acuminata AAA Group Gross Michel เพื่อเป็นอาหารที่มีหน้าที่เฉพาะ - สมฤดี ไทพาณิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objective of this research was to characterize the physicochemical changes that occur in ‘Kluai Hom Thong’ (Musa acuminata AAA Group ‘Gross Michel’) flesh at three ripening stages (stage 6-8) and study the production of banana syrup for functional food from ‘Kluai Hom Thong’ flesh by enzyme processing. It was found that the higher fresh ripe stage of banana at p<0.05 has the following results; the antioxidant activities, moisture content, and reducing sugar are significantly increased. The titratable acidity, total soluble solid, and prebiotic activities score are significantly decreased. The total dietary fiber remains unchanged. Using SHA/GC/MS to characterize volatile compound found that the flavor 17 volatile compounds are varied on banana ripe state. At stage 7, it has maximum major flavor compounds, which consist of 3-Methylbutyl ester, 3-Methyl-, 3-methylbutyl ester and Phenylmethyl ester. Moreover, the results from sensory evaluation show that the ‘Kluai Hom Thong’ flesh in the stage 7 has the most acceptable banana flavor and sweet taste. The data obtained suggests that stage 7 of the ‘Kluai Hom Thong’ flesh was found to be the most suitable raw material for banana syrup production. The effects of heat treatment and anti-browning agents on brown color of ‘Kluai Hom Thong’ pulp were evaluated. The suitable brown color is controlled by adding 0.50 % ascorbic acid (by varying citric acid and ascorbic acid, 0-3.00 %) and 5 minutes heating at 85 ˚C (by varying heat treatment 85 oC for 0-5 minutes). The recommended enzymatic treatment is Pectinex Ultra SP-L® at 1.5 % v/w for 3 hours (by varying commercial enzymes, Pectinex Ultra SP-L® or Sigma P4300®, enzyme concentration 0.5-1.5 % v/w, incubation time 0-12 hours at 32+2˚C). The physicochemical characteristics of banana syrup production are high stability, rich flavor, 27.75% (db) dietary fiber, 8.49 μg DPPH/μg FM (or 421.42 mM TE/g FM) free radical-scavenging activity, prebiotic activity score for Lactobacillus acidophilus LA5 is -0.12, and Bifidobacterium lactic BB-12 is 0.3. Sensory evaluation on the ‘Ka Nom Tuayfoo’ making with the addition of the 20 % banana syrup gave good rating in color, banana flavor, texture and overall acceptability.